The variability of retention in St Helena Bay - Manyakanyaka, Anathi (University of Cape Town, 2021)
The circulation in St Helena Bay and the variability of the retention of the Bay are investigated using seasonal climatologies of the Regional Ocean Modelling System (ROMS). While retention has been studied biologically, the seasonality of the hydrodynamics contributing to the retention have received less attention. In this study we explore how the sea temperature, atmospheric forcing and currents contribute to the seasonal recirculation dynamics in St Helena Bay. Ichthyop, a lagrangian particle tracking method is used to study the spatial variations of local retention rates, with the particles released from the Bay. The circulation on the shelf of the west coast is dominated by upwelling dynamics with the equatorward boundary current, the Benguela Current located just off the shelf. St Helena Bay is protected from the direct impact of the Benguela current by coastal geographical features. A cyclonic circulation pattern is observed in the bay especially in autumn and winter. However, the results suggest that the recirculation patterns are prominent in summer and spring due to the intensification of the Benguela Jet and the nearshore southward current flows along the coast. Similar cyclonic features are observed at 100 m depth in the water column. An analysis of the particle tracking reveals that more drifters are retained in winter than in summer, supported by what is observed in the circulation patterns. Moreover, more drifters are retained in the surface waters than the deep waters.